Successful Treatment of a Patient With Multiple-Line Relapsed Extensive-Stage Small-Cell Lung Cancer Receiving Penpulimab Combined With Anlotinib: A Case Report - Zhang, Zibo; Li, Yujun; Dong, Yan; Li, Jia; Zhang, Bin; Zhang, Chunxia; Cui, Xiaonan (Frontiers in Oncology, 2022)
Small-cell lung cancer (SCLC) is a highly malignant, rapidly developing group of diseases with poor biological behavior. Most patients have extensive-stage SCLC (ES-SCLC) when they are first diagnosed. Standard chemotherapy is prone to relapse in a short period of time, and the patients’ median overall survival (OS) can reach only 13 months when chemotherapy is given in combination with PD-L1 inhibitors. To date, no studies have verified the efficacy and safety of the composite treatment of ES-SCLC with penpulimab and anlotinib despite some recognized data and advantages related to this regimen. Penpulimab, a novel PD-1 inhibitor with an IgG1 subtype, has a structural modification of the Fc segment which can prevent the immune cells from being phagocytosed or killed and can steadily avoid tumor immune escape. This case report describes a 71-year-old man who had ES-SCLC for 7 years which progressed after receiving standard systemic chemotherapy combined with radiotherapy. The third-line treatment of four cycles of anlotinib and carilizumab was discontinued because of grade 2 immune-related pneumonia despite the efficacy being evaluated as stable disease. After maintaining 22 months of progression-free survival, the patient relapsed and switched to a safer regimen of penpulimab combined with anlotinib to continue the treatment for four cycles. Partial response evaluation was confirmed twice, and the patient remained in good general condition. The combination of penpulimab and anlotinib can positively regulate the therapeutic effect by simultaneously acting on the tumor microenvironment and promoting blood vessel normalization. In general, this case provides support for the successful possibility of a rechallenge with immune checkpoint inhibitors, the better clinical efficacy of cross-line therapy with anlotinib, and the drug safety of penpulimab, suggesting a beneficial therapy for the clinical treatment of ES-SCLC.